Pengaruh Komisaris Independen Dan Kepemilikan Institusional Terhadap Konservatisme Akuntansi Pada Perusahaan BUMN - Gerry Hamdani Putra; Denny Novi Satria (Politeknik Ganesha Medan, 2022)
Accounting conservatism is a precautionary principle at the time of financial reporting so that companies are not in a hurry when recognizing and assessing assets and profits so that they can immediately recognize possible losses and debts that may occur, value assets with the lowest value, and take into account liabilities with the highest value. The application of conservatism in making financial statements, an investor can view financial statements transparently and without any element of manipulation contained in the financial statements, because the concept of conservatism is recognizing all losses and recognizing profits only when the profits actually occur. Accounting conservatism is a concept that recognizes expenses and liabilities directly even though there is uncertainty about the outcome, but only recognizes revenues and assets when they are actually received. This study aims to obtain empirical evidence of the effect of independent commissioners and institutional ownership on accounting conservatism. This research is classified as quantitative research. The population in this study are state-owned companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling method used is purposive sampling. The analytical method used is panel data analysis. The number of sample companies used are 17 state-owned companies in a span of 3 years, so the final data used is 51 observational data. The results show that 1) Independent Commissioner has a positive effect on accounting conservatism 2)Institutional ownership has no effect on accounting conservatism